Prognosis Comparison of Use of Oral Anticoagulants and Vitamin K Antagonists in Patients with Intracerebral Hemorrhage - I Made Arya Yogiswara Mahayasa; Puspasari Mahadewi; Luthfiyah Kamila; Ayu Santia Dewi; Muhammad Faeyza; Baiq Wanda Annisa; Arif Setyo; Shania Hafista; Bagas Ekasangga; Adinda Citra; Ulfa Ramdhani; Yusuf Alfian; Arfi Syamsun (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2022)
This study reviewed the literature on the incidence of Intracerebral Hemorrhage (ICH) associated with the use of oral anticoagulant drugs (OAC) and vitamin K antagonists (VKA), then compared the outcomes of using these drugs in terms of mortality, morbidity or prognosis in patients. We did a search on online databases including Pubmed, Google Scholar and Science Direct according to the specified keywords. The results obtained amounted to 935 articles. From these articles, the types of research that met the inclusion and exclusion criteria were then re-screened and the final search results were obtained as many as 10 articles. The results of this study found that of the 10 articles reviewed, 8 of them showed p value > 0.05 so that there was no significant difference between the outcomes of ICH related to OAC or VKA, where outcomes were viewed from the factors of bleeding widening, ICH volume, mortality, and functional impact. Meanwhile, from 2 articles that showed significant results, it was stated that the prognosis of the incidence of ICH related to the use of OAC was better than the use of VKA. Research on ICH, research on original article types, according to predetermined keywords, is a publication in the period 2012-2022, human studies and articles can be accessed.